Development of Smart Ph Stabilizer for Aquarium Fish Tanks Application - Wan Alida Fairuz, Wan Mohamad Hazim; Sahari, Norain (Progress in Engineering Application and Technology, 2023)
Sustaining the pH level of aquarium in the ideal range improves fish growth rate and reduces the incidence of fish death. Currently, to maintain the water quality, humans usually change the water in the aquarium manually when the water looks cloudy and dirty by the naked eyes. However, monitoring and replacement of water manually is time consuming and as water quality changes continuously, it will give an inaccurate result. Therefore, a Smart PH Stabilizer is invented for aquarium application which can monitor the pH level of water. It also changes the water automatically programmed by Arduino UNO to ensure good quality of water for the fish. This device works when the pH fluctuates, the mechanism begins to activate. One of the water pumps will on pump out the contaminated water. After a few minutes, another pump ill pump in a new quality of water. The integration of sensors in the system allows the system to adapt to human reactions, making it more efficient and user pleasant. a Smart PH Stabilizer worked by automatically controlling the pH value in an aquarium tank to generate clean water for aquatic life.